Do external technology acquisitions matter for innovative efficiency and productivity? - Tseveen Gantumur; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
To quickly adapt to technological change and developments, and thus remain competitive, firms increasingly resort to the use of external technology. This paper investigates whether and to what extent the acquisition of external disembodied technology affects the efficiency and productivity in innovation of technology acquiring firms. Using the stochastic frontier analysis combined with a difference-in-difference matching approach and firm-level panel from the German Innovation Survey for the period 1992-2004, we find that manufacturing firms that acquire disembodied technology experience more growth in innovative productivity than non-acquiring firms do. Thus, this study provides evidence on complementarity between internal and external R&D in innovation production, which is attributed by increasing returns to R&D scale and increasing technical efficiency. Moreover, we find that firm size significantly contributes to innovative efficiency and productivity of external technology acquirers.
Keywords: O30; L24; L25; L60; 330; Technology Acquisition; Innovative Efficiency; Innovative Productivity; SFA; Difference-in-Difference Matching; Technologietransfer; Innovation; Technische Effizienz; Produktivität; Schätzung; Deutschland